Studi Komparatif Likuiditas, Leverage, Perputaran Asset, Profitabilitas Dan Harga Saham Sebelum Dan Sesudah Program Makan Bergizi Gratis Pada Perusahaan Sub Sektor Makanan Dan Minuman - Raul Kurniawan; Maria Safitri; Dian Prawitasari; Pradana Jati Kusuma (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The Free Nutritious Meal (MBG) Program is a government policy expected to improve public nutrition while also influencing the food and beverage industry. The implementation of this program may affect companies' financial performance and capital market responses, making it important to examine the differences in corporate conditions before and after the program. This study aims to analyze the differences in the Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Assets (ROA), and stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange before and after the implementation of the Free Nutritious Meal Program. This research employed a quantitative approach using a comparative study design. The sample consisted of 12 companies selected through purposive sampling, resulting in 48 observations before and 48 observations after the implementation of the MBG Program. Data were collected from corporate financial statements and stock price records, then analyzed using the Shapiro–Wilk normality test, followed by the Wilcoxon Signed Rank Test because the data were not normally distributed. The results indicate significant differences in the Current Ratio (p = 0.005), Total Asset Turnover (p = 0.001), Return on Assets (p = 0.011), and stock prices (p = 0.006) before and after the implementation of the MBG Program. In contrast, the Debt to Equity Ratio (p = 0.264) does not show a significant difference. This study concludes that the implementation of the Free Nutritious Meal Program is associated with changes in liquidity, activity, profitability, and market responses of food and beverage companies, while no significant change is observed in their capital structure. These findings are expected to provide useful insights for investors, companies, academics, and policymakers in evaluating the impact of the Free Nutritious Meal Program on corporate performance.